7 MPa Commissioning of Two-phase Flow Loop for Pb-Bi Cooled Direct Contact Boiling Water Small Fast Reactor - Yudi Pramono; Minoru Takahashi; Hiroshi Sofue; Megumi Matsumoto; Fei Huang (Institut Teknologi Bandung, 2005)
One of key issues for the development of the Pb-Bi cooled direct contact boiling water small fast reactor (PBWFR) is thermal-hydraulics. In order to solve the issues of thermal-hydraulics, Pb-Bi-water direct contact boiling two-phase flow loop was designed and constructed, where the loop consisted of a Pb-Bi flow loop, four-heater pin bundle, a chimney, an upper tank with a separator and a dryer, an electromagnetic flow meter, a dump tank, and water supply system, and was operated at the pressure of 7 MPa. Pb-Bi was charged from the dump tank into the Pb-Bi flow loop. Water was circulated by a pump through a preheater, the chimney, the upper tank, a condenser, a buffer tank, and a cooler. A subcooled water was injected into the Pb-Bi in the chimney. Before achieving the next operation phase, commissioning stage was conducted including obtaining of optimal condition of loop, being focused on achievement of the commissioning of the system up to 7 MPa. The experimental results show that steam pressure of 7 MPa was achieved at steam temperature of 286 oC under the saturation condition.